Report on the Presb 60 African Group of Negotiators Experts Support Strategy Meeting - AGNES (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
As a strategy towards enhancing Africa’s participation and preparedness in the global UNFCCC conferences on climate change, the African Group of Negotiators Experts Support (AGNES), in collaboration with partners have over the years been organizing Pre-Strategy Meetings, to consolidate Africa’s positions in various key agenda items. The meetings bring on board negotiators, thematic experts and researchers, civil society organizations, and development partners. The most recent iteration of the strategy meetings (PreSB 60) attracted over 170 diverse delegates from across 31 countries in Africa.